The media relations in communication management and PR of NGOs in times of crisis - Regadera González, Elisa; González Luis, Hildegart; Paricio Esteban, M. Pilar (Estudios sobre el Mensaje Periodístico, 2017)
The present study aims to determine whether the management of relations with the media in some Third Sector organizations has been considered a key element for these entities, especially in times of economic crisis, in which the work of NGOs can be more valued by society, generating information that could make them profitable opportunities proper management thereof. Moreover, we have tried to understand the vision that media professionals have about the work of the Departments, and if the entities with a more professional management of their area of media relations could take this opportunity to promote the achievement of the objectives of their organizations during the crisis.